Adsorptive removal of copper (II) Ions from aqueous solution using a magnetite nano-adsorbent from mill scale waste: synthesis, characterization, adsorption and kinetic modelling studies - Sulaiman, Syazana; Azis, Raba'ah Syahidah; Ismail, Ismayadi; Che Man, Hasfalina; Muhammad Yusof, Khairul Faezah; Abba, Muhammad Umar; Katibi, Kamil Kayode (Springer, 2021)
In this study, magnetite nano-adsorbent (MNA) was extracted from mill scale waste products, synthesized and applied to eliminate Cu2+ from an aqueous solution. Mill scale waste product was ground using conventional milling and impacted using high-energy ball milling (HEBM) for varying 3, 5, and 7 milling hours. In this regard, the prepared MNA was investigated using X-ray diffraction (XRD), high-resolution transmission electron microscope (HRTEM), field emission scanning electron microscopy-energy-dispersive X-ray spectroscopy (FESEM-EDS), UV-Vis spectroscopy, Fourier-transform infrared (FTIR), Brunauer-Emmett-Teller (BET) and zeta potential. The resultant MNA-7 h milling time displayed a crystalline structure with irregular shapes of 11.23 nm, specific surface area of 5.98 m2g-1, saturation magnetization, Ms of 8.35 emug-1, and isoelectric point charge at pH 5.4. The optimum adsorption capacity, qe of 4.42 mg.g-1 for the removal of Cu2+ ions was attained at 120 min of contact time. The experimental data were best fitted to the Temkin isotherm model. A comparison between experimental kinetic studies and the theoretical aspects showed that the pseudo-second-order matched the experimental trends with a correlation coefficient of (R2 > 0.99). Besides, regeneration efficiency of 70.87% was achieved after three cycles of reusability studies. The MNA offers a practical, efficient, low-cost approach to reutilize mill scale waste products and provide ultra-fast separation to remove Cu2+ from water.